Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0127626
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Stress Responses of Reintroduced Tigers in Relation to Anthropogenic Disturbance in Sariska Tiger Reserve in India

Abstract: Tiger (Panthera tigris), an endangered species, is under severe threat from poaching, habitat loss, prey depletion and habitat disturbance. Such factors have been reported causing local extermination of tiger populations including in one of the most important reserves in India, namely Sariska Tiger Reserve (STR) in northwestern India. Consequently, tigers were reintroduced in STR between 2008 and 2010, but inadequate breeding success was observed over the years, thus invoking an investigation to ascertain phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…Post-release monitoring in these cases was not done adequately due to various reasons including non-deployment of telemetry devices and long-term monitoring strategy. A similar reintroduction effort in Sariska Tiger Reserve in the state of Rajasthan in India met with low breeding success (Sankar et al 2010) due to anthropogenic causes (Bhattacharjee et al 2015;Ramesh et al 2015), primarily offering home range knowledge on founder individuals. In other studies in Russia involving captive Siberian tigers, where one adult Siberian male and two young female tigers were released from the Otis rehabilitation Centre into the wild, the ultimate fate of the male remains unclear, while the two other females died during the monitoring period (Miquelle et al 2001;Goodrich and Miquelle 2005), although recent efforts are being made.…”
Section: Discussionmentioning
confidence: 99%
“…Post-release monitoring in these cases was not done adequately due to various reasons including non-deployment of telemetry devices and long-term monitoring strategy. A similar reintroduction effort in Sariska Tiger Reserve in the state of Rajasthan in India met with low breeding success (Sankar et al 2010) due to anthropogenic causes (Bhattacharjee et al 2015;Ramesh et al 2015), primarily offering home range knowledge on founder individuals. In other studies in Russia involving captive Siberian tigers, where one adult Siberian male and two young female tigers were released from the Otis rehabilitation Centre into the wild, the ultimate fate of the male remains unclear, while the two other females died during the monitoring period (Miquelle et al 2001;Goodrich and Miquelle 2005), although recent efforts are being made.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between stress and gastritis is, however, likely multifactorial since although the highest ACMR were from cheetahs with gastritis, some affected animals had very low ACMR and a few non‐affected cheetahs had high ACMR. This individual variability in stress responses is known to occur in cheetahs [Wielebnowski et al, ; Terio et al, , ; Wells et al, ; Ludwig et al, ; Koester et al, ] as well as in domestic cats [Galuppi et al, ; Ellis et al, ], jaguars [Conforti et al, ], and tigers [Bhattacharjee et al, ]. Other factors, such as diet, also affect the development of gastritis [Lane et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of captive clouded leopards (Neofelis nebulosa), where reproductive success in captivity has been poor, Wielebnowski et al (2002) observed increased GC concentrations in individuals with small enclosure heights and limited keeper contact. Alternatively, anthropogenic factors, such as human activity from roads and villages, could be a source of stress in free-ranging but not captive populations (Bhattacharjee et al, 2015;Van Meter et al, 2009). It is difficult to determine whether stressors in captivity are more severe than those in a free-ranging environment, particularly as some individuals may cope with stress better than others (Ladewig, 2000;Millspaugh and Washburn, 2004;Sapolsky, 1994), and repeated exposure may diminish stress responses through habituation (Ladewig, 2000).…”
Section: Introductionmentioning
confidence: 99%